2011
DOI: 10.1002/cncr.26492
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of insulin receptor expression on survival of patients with nonsmall cell lung cancer

Abstract: Background The purpose of this study was to characterize insulin receptor (IR) and insulin-like growth factor-1 receptor (IGF-1R) expression in patients with non-small cell lung cancer (NSCLC). Methods A total of 459 patients who underwent curative resection of NSCLC were studied (median follow-up duration, 4.01 years). Expression of the IR and IGF-1R protein in tumor specimens was assessed immunohistochemically using tissue microarrays. Results The cytoplasmic IR score was higher in patients with adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…NSCLC expresses the insulin receptor, and high levels of insulin receptor expression have been associated with faster cancer progression and decreased survival (35). Metformin reduces insulin resistance and circulating insulin levels, thereby attenuating the stimulatory effect of insulin (36).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC expresses the insulin receptor, and high levels of insulin receptor expression have been associated with faster cancer progression and decreased survival (35). Metformin reduces insulin resistance and circulating insulin levels, thereby attenuating the stimulatory effect of insulin (36).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that high expression level of IGF-IR was associated with poor survival of patients with various types of cancer (10). Up to date, limited data exist on clinical significance of IGF-IR expression in lung cancer, and the association between IGF-IR and poor prognosis remains controversy (27,28). In this study, we found that IGF-IR could mediate the formation of a novel b-catenin/POU5F1/SOX2 complex in LACSLCs to play a crucial role in self-renewal of lung cancer cells and predict poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, a high level of IR expression is indicative of poor survival [92,93]. Overexpression of IR predicts poor survival also in patients with nonsmall cell lung cancer [94]. The interpretation of these data is complicated because circulating insulin levels were not reported.…”
Section: Insulin Receptors As Prognostic Markers In Cancermentioning
confidence: 99%